2021
DOI: 10.14740/jh824
|View full text |Cite
|
Sign up to set email alerts
|

Does ABO Blood Groups Affect Outcomes in Hospitalized COVID-19 Patients?

Abstract: Background Blood group type A has been associated with increased susceptibility for coronavirus disease 2019 (COVID-19) infection when compared to group O. The aim of our study was to examine outcomes in hospitalized COVID-19 patients among blood groups A and O. Methods This is an observational study. Kruskal-Wallis and Chi-square tests were used to compare continuous and categorical variables. Multivariable logistic regression models were used to examine association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Univariate analysis revealed that ABO Blood Group was not a risk factor for hypercoagulability in COVID-19 patients. These findings are consistent with some previous studies (Kumar et al, 2021;Rao et al, 2021) and contradict others (Marcos et al, 2020). The association between ABO blood group and thrombosis risk has been confirmed by many studies.…”
Section: Abo Blood Groups and Hypercoagulability In Covid-19 Patientssupporting
confidence: 93%
“…Univariate analysis revealed that ABO Blood Group was not a risk factor for hypercoagulability in COVID-19 patients. These findings are consistent with some previous studies (Kumar et al, 2021;Rao et al, 2021) and contradict others (Marcos et al, 2020). The association between ABO blood group and thrombosis risk has been confirmed by many studies.…”
Section: Abo Blood Groups and Hypercoagulability In Covid-19 Patientssupporting
confidence: 93%
“…Most ABO studies have been focused on the incidence and severity of COVID-19 [ 17 ], and few studies on symptoms and complications post-COVID-19. Some studies found that the O group offered protection against COVID-19 infection, whereas A-group subjects experienced a higher risk of adverse outcomes [ 12 , 13 , 39 , 40 ], with more cardiovascular complications in the A-group subjects [ 41 ], whereas subjects in the B group experienced more severe illnesses and higher fatality rates [ 11 , 15 , 22 , 41 , 42 ], but no ABO blood group differences in mortality were found in other studies [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multicenter retrospective research of Hoiland et al aimed at investigating if ABO blood types are linked to various severities of COVID-19 among ICU admitted patients and found that [31] There were no significant variations in rates of ICU admissions, MV, vasopressors, acute renal failure, venous thromboembolism, and readmission rate between blood types A and O, according to Kumar et al [32] Non-O classes had a slightly higher infection prevalence, according to Zietz et al When compared to type O, the risk of intubation was lower for type A and higher for types of AB and B. In contrast, the mortality risk was higher for type AB and lower for types A and B.…”
Section: Discussionmentioning
confidence: 99%